Effectiveness of Providing Non-Pharmacological Inspiratory Muscle Training Therapy on Reducing Dyspnea in Copd Patients: Systematic Review - Arisudhana, Gede Arya Bagus; Hendry, Zul (South East Asia Nursing Research, 2024)
Background: COPD is one of a group of non-communicable diseases that has become a public health problem in Indonesia. The main problem of COPD patients is dyspnea.Objective: The aim of this review is to determine the effectiveness of using non-pharmacological inspiratory muscle training therapy to reduce shortness of breath (dyspnea) in COPD sufferers.Method: Articles were obtained through searches on Medline, Scient Direct, Proquest, and Google Scholar. Inclusion and exclusion criteria in this systematic review are types of studies of non-pharmacological inspiratory muscle training therapy that have been proven to be significant and effective in alleviating dyspnea in COPD sufferers that have been published in peer-reviewed ways, and use English. The design used was an RCT, the type of respondents were adults (over 17 years of age). Published from 2015-2015. Literature assessment uses critical appraisal guidelines and casptools.Results: There were five studies that found changes in the average value of maximal inspiratory pressure (PImax), but no changes were found in lung functional capacity. Inspiratory Muscle Training has been proven to be effective in reducing dyspnea, where the inspiratory respiratory muscles are trained to restore their strength so that they can carry out maximum inspiration and have better lung tolerance for activity.Conclusion: IMT can be useful for adult COPD patients and can reduce the patient's hospital stay.